5 Rifaximin prophylaxis against travellers' diarrhoea does nor increase acquisition of extended-spectrum ß – lactamase producing enterobacteriaceae (ESBL-E) in a UK military population travelling to Kenya. Issue 5 (26th September 2022) - Troth, Tom; Burns, Daniel; Porter, Chad; Rimmer, Joanna; Fraser, Jamie; Lalani, Tahaniyat; Tribble, David; Schaik, Willem Van; Gutierrez, Ramiro
Abstract : Background: Travellers' Diarrhoea (TD) is a significant issue for deployed troops. Antibiotic prophylaxis can be effective but raises antimicrobial resistance (AMR) concerns. PREVENT TD study, was a double-blind, randomised, placebo-controlled trial comparing once- and twice-daily rifaximin 550mg against placebo (ClinicalTrials.gov: NCT02498301 ). Rifaximin showed a protective effect (0.05 vs 0.36/100 person days, p= 0.025 vs placebo) against incident TD. Here we present our results on the acquisition of ESBL-E in PREVENT TD participants. Methods: Enrolled UK subjects deployed to Kenya for 6-week periods. 121 participants provided stool samples upon arrival and prior to departure. Approximately 100mg of stool was incubated in Luria Broth with cefotaxime (10 μg/ml) at 37°C overnight. Cultures were then spread onto ESBL Chromoselect agar and incubated again overnight. Growth was taken as positive for ESBL-E bacteria. The two rifaximin intervention arms were compared to placebo using Fisher's exact test. Bioinformatic analysis has been performed using Parsnp, MLST and Abricate programs. Results: 84/121 (69.4%) subjects had no ESBL-E present on arrival in Kenya. The highest incidence of ESBL acquisition was observed in subjects randomised to the placebo arm; however, the differences were not statistically significant (table in presentation). In the cohorts colonised with ESBL-E at the start of the study, there was a non-statistically significant reduction in the ESBL-E rates with those taking rifaximin prophylaxis. Genome sequencing showed a number of ESBL-E E. coli are genetically very similar suggesting a source in Kenya. Conclusions: While ESBL acquisition rate was relatively high (26.5%), rifaximin was not associated with an increase in ESBL acquisition. Further work will be performed to investigate acquisition of rifaximin resistance among commensal Enterobacteriaceae during the trial. Further Bioinformatic work is ongoing looking at acquisition of resistance genes.